2019
DOI: 10.1080/10502556.2019.1699372
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenerational Effects of Parental Divorce on Young Adult Relationships

Abstract: Due to the current high rates of divorce, many young adults have experienced the effects of parental divorce. Although a variety of research has investigated both the positive and negative implications of divorce for individuals, relatively little research has looked at the relationship effects of parental divorce. Yet divorce likely influences both parent-child relationships (especially with a non-custodial parent) and young adult romantic relationships. The purpose of this study was to explore more fully how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2121
2121

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
(176 reference statements)
0
13
0
4
Order By: Relevance
“…According to the findings of this study, early divorce children were frequently considered to be more scared and depressed than offspring from intact homes. Information on the typical reaction of a certain age and socioeconomic groups to familial divorce is needed to build effective preventative treatments (Rootalu and Kasearu, 2016;Roper et al, 2020;Rudd et al, 2016). As a result, more research into the adaptation of divorced children and the factors that influence this adjustment is required.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of this study, early divorce children were frequently considered to be more scared and depressed than offspring from intact homes. Information on the typical reaction of a certain age and socioeconomic groups to familial divorce is needed to build effective preventative treatments (Rootalu and Kasearu, 2016;Roper et al, 2020;Rudd et al, 2016). As a result, more research into the adaptation of divorced children and the factors that influence this adjustment is required.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that emotional divorce is more harmful than legal divorce. Problematic parental relationships also adversely affect their children's relationships later in adulthood (Roper, Fife & Seedall 2020;Fraley & Hefferman 2013). The psychological and personal characteristics of individuals are of considerable importance in their marriage.…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Although a history of parental divorce or separation appears to increase risk for negative relational outcomes, many adult children of divorced or separated parents do not experience these difficulties. In fact, some report relational benefits resulting from parental divorce, including closer relationships with siblings and other family members and expansion of social networks (Halligan et al, 2014;Roper et al, 2020). There is also evidence that the association between parental divorce and negative outcomes may be decreasing as divorce has become more common and less stigmatized (Auersperg et al, 2019).…”
Section: Effects Of Parental Divorce/separation On Attachment Securitmentioning
confidence: 99%